Utilization of newly developed immobilized enzyme reactors for preparation and study of immunoglobulin G fragments - Korecká, Lucie; Bílková, Zuzana; Holèapek, Michal; Královský, Josef; Benes, Milan; Lenfeld, Jiøí; Minc, Nicolas; Cecal, Roxana; Viovy, Jean-Louis; Przybylski, Michael (Journal of chromatography. B, Analytical technologies in the biomedical and life sciences, 2004)
The newly developed immobilized enzyme reactors (IMERs) with proteolytic enzymes chymotrypsin, trypsin or papain were used for specific fragmentation of high molecular-mass and heterogeneous glycoproteins immunoglobulin G (IgG) and crystallizable fragment of IgG (Fc). The efficiency of splitting or digestion were controlled by RP-HPLC. The specificity of digestion by trypsin reactor was controlled by MS. IMERs (trypsin immobilized on magnetic microparticles focused in a channel of magnetically active microfluidic device) was used for digestion of the whole IgG molecule. The sufficient conditions for IgG digestion in microfluidic device (flow rate, ratio S:E, pH, temperature) were optimized. It was confirmed that the combination of IMERs with microfluidic device enables efficient digestion of highly heterogeneous glycoproteins such as IgG in extremely short time and minimal reaction volume.
Keywords: Electrophoresis, Polyacrylamide Gel; sekvence aminokyselin; spektroskopie infračervená s Fourierovou transformací; Mass Spectrometry; hmotnostní spektrometrie; Immunoglobulin G; imunoglobulin G; bioreaktory; Chromatography, High Pressure Liquid; Enzymes; imunoglobuliny - fragmenty; Immunoglobulin Fragments; vysokoúčinná kapalinová chromatografie; Spectroscopy, Fourier Transform Infrared; elektroforéza v polyakrylamidovém gelu; molekulární sekvence - údaje; enzymy; Molecular Sequence Data; Bioreactors; Amino Acid Sequence